Hubungan antara Nature Relatedness dan Kecemasan pada Generasi Muda Daerah Perkotaan - Karunia Putri; Charina F. Y. Tyas; Dewita D. Ngenggar; Gabriel W. Adhara; Anjelinus V.A. Hari; Meisi Cahyani; Bartolomeus Yofana Adiwena (Fakultas Psikologi Universitas Pancasila, 2023)
Mental health concerns are a significant issue worldwide, and Indonesia is no exception. In Indonesia, approximately 15.5 million teenagers (34.9%) experience mental health problems, with anxiety disorders being the most prevalent. The lack of green spaces in urban areas and high work demands prevent young people from connecting with nature. Furthermore, urban life is practical, and many teenagers prefer indoor activities with technological entertainment, which further reduces their exposure to nature. To investigate the relationship between nature-relatedness and anxiety in the urban young generation, a research study was conducted. The study employed a quantitative-correlational research method and utilized the Nature Relatedness Scale and State-Trait Inventory for Cognitive and Somatic Anxiety (STICSA) to measure the participants. 93 participants met the participant’s criteria and completed the questionnaire, and the data was analyzed using the Product Moment correlation technique. The research findings indicate that there is no correlation between nature-relatedness and anxiety. Researchers speculate that nature-relatedness primarily benefits individuals by increasing positive emotions rather than reducing negative emotional states such as depression. However, urban residents can still enjoy nature through artificial environments, such as visiting green parks and observing sky views. The availability of artificial environments enables urban communities to remain close to nature without experiencing anxiety.